hngl.net
当前位置:首页 >> (-5/12)×8/15÷(-2/3) >>

(-5/12)×8/15÷(-2/3)

(-5/12)×8/15÷(-2/3) =5/12X8/15X3/2 =(5X8X3)/(12X2X15) =1/3

(8/15-2/5)÷12 =(8/15-6/15)÷12 =2/15÷12 =2/15×1/12 =1/90

(-5╱12)×8╱15×1╱2×(-2╱3) =5/12×8/15×(1/2×2/3) =1/3×2/3×1/3 =2/27

2/5÷(12/5)×(-2)³-(-4/3)²×(-3/16) =2/5×5/12×(-8)-16/9×(-3/16) =-4/3+1/3 =-1

(4/7)÷(-2又2/5)-(3/7×5/12-5/3) =4/7÷(-12/5)-3/7×5/12+5/3 =-4/7×5/12-3/7×5/12+5/3 =5/12×(-4/7-3/7)+5/3 =5/12×(-1)+5/3 =-5/12+5/3 =15/12 =5/4

(2/3-2/5)除以(1/8+5/12) =(2/3×24-2/5×24)除以(1/8×24+5/12×24) =(16-9.6)除以(3+10) =6.4÷13 =64/130

3/5x5/12÷3/2= =1/4x2/3 =1/6 8÷2/5x1/4 =8x5/2x1/4 =20x1/4 =5 (1/3-1/4)x12 =1/3x12-1/4x12 =4-3 =1

收到了吗?

(1)原式=12-8+11-2-12=4+11-2-12=15-2-12=13-12=1;(2)原式=118÷13=118×3=16;(3)原式=(-1)3×(-5)÷[-9+4]=(-1)×(-5)×(-15)=5×(-15)=-1.

网站首页 | 网站地图
All rights reserved Powered by www.hngl.net
copyright ©right 2010-2021。
内容来自网络,如有侵犯请联系客服。zhit325@qq.com